Efeito imunomodulador de CXCL10 na infecção de macrófagos murinos por cepa de Leishmania braziliensis isolada de paciente refratário ao tratamento com antimônio - Rodrigues, Naya Lúcia de Castro (2015)
Chemotherapy available for leishmaniasis is effective in many cases, however is still not satisfactory, presenting several inconveniences, one of them, resistance to antimony, which is a major current problems. Few studies using treatment with recombinant chemokines for leishmaniasis have been reported. The objective of this study was to evaluate the immunomodulatory effect in vitro of CXCL10 and its association with Glucantime for the infection of macrophages by Leishmania braziliensis strain refractory to treatment with antimony. For this, murine macrophages were infected with L. braziliensis and treated or not with CXCL10 (25, 50 e 100ng/mL), Glucantime (32mg/mL), and CXCL10+Glucantime [(25, 50 e 100ng/mL) + (32mg/mL)]. After 24 and 48h of infection were evaluated: parasitic load (macrophages infected count on coverslips stained), nitric oxide concentration (NO) and the pattern of the cytokines TNF-α, IL-12, IL-4, IL-10, and TGF-β in the culture supernatant. The results showed that the treatment with CXCL10 and CXCL10+Glucantime combination resulted in a significant reduction of the parasitic load, ranging from 70.5% to 95% and 92.4% and 95.0%, respectively, compared with the control untreated, while treatment with Glucantime decreased infection of macrophages to 74.0%. The reduction of the parasitic load was correlated with the increase of NO in all concentrations of CXCL10 (p <0.001). However, it was not observed the same dynamic when it was used to CXCL10+Glucantime association. TNF-α and IL-12 levels increased as a function of the concentration of CXCL10 in the first 24h, however, was inhibited when the infected macrophages were treated with Glucantime (p <0.05). The concentration of TNF-α was lower in cells treated with CXCL10+Glucantime than in those treated only with CXCL10 in both time periods. To the association CXCL10+Glucantime the IL-12 only induced a significant production within 24h when CXCL10 was used at a concentration of 100ng/ml (p <0.01). CXCL10 and association CXCL10+Glucantime treated cells showed a decrease of IL-4 concentration decreasing as the chemokine concentrations were higher (p <0.01) while treatment with Glucantime had a high production of this cytokine. In both times evaluated, treatment with CXCL10 induced IL-10 production at concentrations of 50ng/ml, and 100ng/ml, induced a 3-fold more IL-10 (p <0.001) when compared with antimony or with association CXCL10+Glucantime. TGF-β showed different behavior in the two time periods, an increase in the early hours, and fall in the past 48h. Glucantime induced TGF-β concentration higher than that induced by CXCL10. The association CXCL10+Glucantime showed increased production of TGF-β inverse of the concentration of CXCL10 used. In conclusion, in vitro treatment with CXCL10 induced a Th1 response profile (increase of TNF-α, and IL-12), controlling the intracellular parasitemia and modulation of the inflammatory response mediated by IL-10, in macrophages infected with L. braziliensis refractory to antimony. The Glucantime+CXCL10 association, although it has reduced parasitic load, not inducing a significant increase in nitric oxide, and showing a induction of TNF-α, IL-12 and reduction IL-4,.